(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Retuerma-Dioneda A, Alejandro GJD. 2022. Inventory of Annonaceae in Abasig-Matogdon-Mananap Natural Biotic Area, Camarines Norte, Bicol, Philippines. Biodiversitas 23: 2213-2224. The Abasig-Matogdon-Mananap Natural Biotic Area (AMMNBA) is a protected area home to endemic plants; however, Annonaceae remains understudied. The study provided a checklist of Annonaceae species in the area and their taxonomic keys, endemicity and conservation status. Field surveys were conducted in January 2020 and July 2021 in San Vicente and Labo, Camarines Norte. The 110 species identified belong to 11 genera- Artabotrys, Drepananthus, Fissistigma, Friesodielsia, Goniothalamus, Meiogyne, Monoon, Phaeanthus, Polyalthia, Popowia, and Uvaria and five (5) tribes: Ambaviodeae, Annoneae, Miliuseae, Uvarieae, and Xylopieae. Four (4) endemic species were recorded: Friesodielsia lanceolata, Polyalthia luzonensis, Polyalthia lanceolata and Goniothalamus elmeri. This study provides baseline information on Annonaceae species in AMMNBA for appropriate conservation policies and proper management of the potential economic benefits.